The use of lexical bundles in English language academic writing among university learners: a systematic literature review - Haji Darmi, Ramiza; Chen, Dan; MD Yusof, Mohamad Ateff (Sciedu Press, 2024)
Lexical bundles have been widely studied in English academic writing, but not as extensive in university learners‟ academic writing. This study conducted a systematic review of the literature on lexical bundles in academic writing among university learners from 2017 to 2022 to describe the directions of and limitations of recent studies on how lexical bundles influence the fluency and coherence of academic writing among university learners. The review relied on two major databases, Scopus and Web of Science, and adhered to the PRISMA 2020 guidelines. The study analyzed 28 articles them based on three content-based themes: the research context, the research contents, and the research objectives. Recent research on lexical bundles in academic writing among university students 1) lacks an in-depth analysis of specific functions, such as text-oriented bundles, which predominate and play an important coherence role in more advanced academic writing; 2) addressing the analysis of lexical bundles solely through a phraseological lens fails to account for their genre-specific characteristics. It is crucial to merge insights from both genre and phraseology for a thorough analysis; 3) comparing the academic writing of native English-speaking learners, that of university learners in East Asia and the Middle East are unevenly distributed and limited in scope. There is limited research on academic writing at higher academic levels, university learners in Southeast Asia, and cross-regional comparative studies.